2015
DOI: 10.1124/jpet.115.229740
|View full text |Cite
|
Sign up to set email alerts
|

Creation of Apolipoprotein C-II (ApoC-II) Mutant Mice and Correction of Their Hypertriglyceridemia with an ApoC-II Mimetic Peptide

Abstract: Apolipoprotein C-II (apoC-II) is a cofactor for lipoprotein lipase, a plasma enzyme that hydrolyzes triglycerides (TGs). ApoC-II deficiency in humans results in hypertriglyceridemia. We used zinc finger nucleases to create Apoc2 mutant mice to investigate the use of C-II-a, a short apoC-II mimetic peptide, as a therapy for apoC-II deficiency. Mutant mice produced a form of apoC-II with an uncleaved signal peptide that preferentially binds high-density lipoproteins (HDLs) due to a 3-amino acid deletion at the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 58 publications
2
31
0
Order By: Relevance
“…The recent development of an apoC-II mimetic peptide, which incorporates the third helix of apoC-II, has shown some promise as potential future therapy. Intravenous injection of this peptide normalized TG in a mouse model of apoC-II deficiency 81 . Furthermore, the apoC-II mimetic peptide potentiated LPL activity in other non-apoC-II deficient HTG conditions, suggesting a potential broader utility 93 .…”
Section: Clinical Therapy For Apolipoprotein C-ii Deficiencymentioning
confidence: 93%
See 1 more Smart Citation
“…The recent development of an apoC-II mimetic peptide, which incorporates the third helix of apoC-II, has shown some promise as potential future therapy. Intravenous injection of this peptide normalized TG in a mouse model of apoC-II deficiency 81 . Furthermore, the apoC-II mimetic peptide potentiated LPL activity in other non-apoC-II deficient HTG conditions, suggesting a potential broader utility 93 .…”
Section: Clinical Therapy For Apolipoprotein C-ii Deficiencymentioning
confidence: 93%
“…4A). Retention of the signal peptide in transgenic mice due to a specific mutation has recently been shown to cause the selective binding of apoC-II to HDL, leading to HTG 81 . ApoC-II contains no N-linked glycosylation sites and does not appear to undergo significant O-linked glycosylation.…”
Section: Apoc-ii Biochemistrymentioning
confidence: 99%
“…Further, in vivo evaluation of the peptide in the APOE −/− mouse model showed significant activity of lowering plasma triglycerides and plasma cholesterol. Further evaluation of the same peptide in APOC2 mutant mice showed the ability to correct the hypertriglyceridemia in these mice [146]. Although preliminary in nature, these studies provide crucial proof-of-concept validation for APOC2 mimetic peptides as pharmacological tools.…”
Section: Pharmacological Targeting Of Lplmentioning
confidence: 99%
“…Deficiencies of LPL inhibitors, such as apoC-III or angiopoietin-like proteins, conferred protective effects against atherosclerosis 18, 19 . In contrast, it has been shown that the loss of apoC-II LPL activator increased the risk of CVD in parallel with plasma TG and cholesterol levels 20, 21 .…”
Section: Introductionmentioning
confidence: 95%